Navigating Cultural Nuances In Quantitative Consumer Research: Methodological Adaptations For Studying Millennials In Sabah, Malaysia - Carrey Oliver; Rozaini Binti Rosli Lincoln (International Journal Labs, 2025)
This paper presents the methodological adaptations for conducting quantitative consumer research in culturally nuanced contexts, using a study of millennial purchase intention in Sabah, Malaysia, as a case study. The application of standard quantitative methods in non-Western, collectivist, and digitally diverse settings presents unique challenges (Jack- son and Wang, 2013; Muk et al., 2014; Zimu, 2023). This article details specific adap- tations in research philosophy, sampling, data collection, and bias mitigation to address these issues. The key contribution is a practical framework for maintaining methodolog- ical rigour while accounting for cultural and economic variations. The study specifically adapted established measurement scales to include geographical and demographic refer- ences to Sabah and millennials, utilized diverse recruitment channels to mitigate sampling bias, and implemented procedural and statistical safeguards to address potential common method bias in a collectivist setting.